A cross-cultural comparison of German and Canadian student teachers' assessment competence. Issue 1 (2nd January 2020) - DeLuca, Christopher; Schneider, Christoph; Coombs, Andrew; Pozas, Marcela; Rasooli, Amirhossein
ABSTRACT: Teachers' competence in educational assessment is a key feature in teacher professionalism. Understanding of assessment competence has evolved from the learning of technical skills in assessment to a context-dependent, socially defined understanding encompassing a multitude of approaches to assessment. Thus, a holistic approach to assessment competence is used in this research to specifically consider the role of education culture on assessment competence. In particular, we compared Canadian and German student teachers with regard to their self-rated competence in, and approaches towards, educational assessment. While structural analysis revealed that the overall dimensions in which assessment is perceived do not depend on culture, ANOVAs pointed at some differences between the two countries, particularly concerning assessment purposes and approaches to fairness.